2017
DOI: 10.3390/ijms18112305
|View full text |Cite|
|
Sign up to set email alerts
|

Receptors for Insulin-Like Growth Factor-2 and Androgens as Therapeutic Targets in Triple-Negative Breast Cancer

Abstract: Triple-negative breast cancer (TNBC) occurs in 10–15% of all breast cancer patients, yet it accounts for about half of all breast cancer deaths. There is an urgent need to identify new antitumor targets to provide additional treatment options for patients afflicted with this aggressive disease. Preclinical evidence suggests a critical role for insulin-like growth factor-2 (IGF2) and androgen receptor (AR) in regulating TNBC progression. To advance this work, a panel of TNBC cell lines was investigated with all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…We have also shown that in TNBC cell lines that activation of ERβ results in increased secretion of IGF2 which can bind to IR/IGF1R, and activate growth promoting capabilities. Recent studies have shown that targeting the IGF1R pathway could be a therapeutic target [ 65 , 66 ]. These results and the previous data suggest that endocrine therapy may be beneficial for improving TNBC outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…We have also shown that in TNBC cell lines that activation of ERβ results in increased secretion of IGF2 which can bind to IR/IGF1R, and activate growth promoting capabilities. Recent studies have shown that targeting the IGF1R pathway could be a therapeutic target [ 65 , 66 ]. These results and the previous data suggest that endocrine therapy may be beneficial for improving TNBC outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…By interaction with specific tyrosine-kinase receptors, insulin-like growth factor-1 receptor (IGF1R) and insulin receptor isoform A (IR-A), IGF2 stimulates downstream actions via the mitogen-activated protein kinase (MAPK) and phosphatidylinositol 3kinase (PI3K) AKT/protein kinase B (PKB) pathways to stimulate tumor proliferation 9 . A recent study highlights the significant anti-proliferative activities of IGF1R and IR antagonists in TNBC cells in vitro 10 . BMS-754807, an established IGF1R/IR inhibitor, and NVP-AEW541, an IGF1R inhibitor, exhibit anti-proliferative effects on IGF2-expressing TNBC cells, an action dependent in part on AKT activity.…”
Section: Discussionmentioning
confidence: 99%
“…It promotes the growth of triple-negative breast cancer cells through autocrine and/or paracrine mechanisms. The mechanism may be related to androgen receptor (AR) and estrogen receptor (ER b) (144,145). Therefore, two-way targeted therapy for the IGF-II, AR and ER b signaling pathways is expected to be a potential target for TNBC treatment.…”
Section: Insulin-like Growth Factor-ii (Igf-ii) and Tumorsmentioning
confidence: 99%